Application of Arduino Uno in A Hydroponic System in An Automatic Mixing and Nutrition Process - Sukma, Rexy Khoerul; Ruuhwan, Ruuhwan; Anwar, Dede Syahrul (Jurnal Prajaiswara, 2024)
The conversion of agricultural land into residential areas has implications for the reduction of agricultural productivity, thereby disrupting the food supply among communities. One alternative to increase food supply is hydroponic farming. Hydroponics is worth considering, as it only requires minimal land. However, hydroponic cultivation also has its own challenges. One of them is the concentration of water, nutrient A, and nutrient B that must be considered. The lack of nutrient supply to plants will slow down plant growth, while excessive nutrient application can cause plant stress. To avoid these issues, one way is through the application of Arduino UNO in hydroponic systems, where the sensors on Arduino will measure the dissolved substances in water in parts per million (PPM). With the application of Arduino in hydroponic systems, the concentration of nutrients A and B will be more accurate, and nutrient application can be done automatically.